Service-Learning as a Practical Introduction to Undergraduate Public Health: Benefits for Student Outcomes and Accreditation - Mason, Meghan R.; Dunens, Elizabeth (Frontiers in Public Health, 2019)
Since the mid-1980s, service-learning has gained recognition as a pedagogical model in higher education with exciting potential for students’ academic, civic, and professional development. Deemed a high-impact educational practice by the American Association of Colleges and Universities, extant research points to student learning, engagement and retention benefits from community-based experiences integrated into curriculum. Numerous studies have examined best practices for service-learning from varying stakeholder perspectives (faculty, student, community partner) and disciplines; however, due to the recent development of public health as a major offering in U.S. undergraduate education, the value of service-learning within the discipline should be further explored. While recommendations for service-learning in undergraduate public health programs have been provided, no evaluation of the impact on student learning outcomes has been conducted. This study presents one university’s model of service-learning in introductory public health courses and resulting data that supports the use of service-learning to advance student achievement of foundational domains as outlined by the Council on Education for Public Health.